AKTIVITAS KERJA DAN PENGHASILAN PENARI DI RAMAYANA BALLET PURAWISATA YOGYAKARTA - Endang Sutiyati (Jurnal Penelitian Humaniora, 2007)
This research aims: (1) to find work activity of all dancers in Ramayana Ballet Purawisata and (2) to get information of how much money do they earn. To achieve the goal, data collection is conducted through depth and repeated interview. The research uses a descriptive-analytical technique so that a complete description of the work activity and income of dancers in Ramayana Ballet Purawisata can be obtained. The research finds that: (1) The performance of the dancers is good enough, in term that each of the dancers are competing not to come late since if they did so, their character will be immediately substituted by others. (2) They try to improve themselves by continuous training out of the determined dancing schedule. (3) Senior dancers are actively involved in administration staff. And (4) in addition to salary received monthly, they deserve the right to get additional incomes and holiday subsidy